Effect of the Sn dopant on the crystallization of amorphous Ge2Sb2Te5 films induced by an excimer laser. (November 2015) - Bai, N.; Liu, F.R; Han, X.X; Zhu, Z.; Liu, F; Lin, X.; Sun, N.X.
Abstract: In this paper, the influence of Sn doping (0%, 8%, and 14%) on the crystallization of Ge2 Sb2 Te5 (GST) was studied with the aid of an ultraviolet laser. It was found that the addition of Sn element not only expanded the lattice parameter but also decreased the crystallization temperature and activation energy as compared to the GST. As compared to the Ge2 Sb2 Te5, a more complete crystallization of the Sn doping Ge2 Sb2 Te5 is mainly due to the lower binding energy of Sn–Te (359.8 kJ/mol), which could be more easily taken part in the bond breakage and formation than Ge–Te (456 kJ/mol) in such a short time as 30 ns. The equiaxial grains were obtained for the Sn8 Ge15 Sb23 Te54 films when crystallization was induced by the laser fluence of 20 mJ/cm 2 but the grains elongated when the laser fluence was increased to 60 mJ/cm 2 . The reason may be the incorporation of Sn elements changed the crystal nucleation mode. Highlights: The crystallization behavior of Sn-doped GST were studied. The crystallization temperature and activate energy of the Sn-doped GST were obtained. The Sn-doped GST crystallized more completely as compared with the pure GST. Sn elements changed the crystal nucleation mode.